Direct observation of dynamic protein interactions involving human microtubules using solid-state NMR spectroscopy - Yanzhang Luo (Nature Portfolio, 2020)
Microtubule (MT) organization is regulated by many microtubule-associated proteins (MAPs) that contain intrinsically disordered regions. Here authors produce [13C, 15N] labeled, functional microtubules from human cells for solid-state NMR which allows studying MAP-MT interactions.